2022
DOI: 10.15282/ijame.19.2.2022.06.0748
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of a Three Fluid Heat Exchanger Used in Domestic Heating Applications

Abstract: Recent work analytically investigates the heat transfer characteristics of a three fluid heat exchanger used for domestic heating applications with respect to different design parameters, i.e. flow rate, inlet temperature, tube diameter, coil diameter, and coil pitch. The present and previous results are compared with the literature. Overall agreement among these results are observed with little variation. Afterwards, the present temperature data was verified with prior experimental data and little deviation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Also, they found that the parallel flow is less effective than counter flow arrangement. Taraprasad et al 7 have investigated the performance of a TFHE used in domestic heating application. In this investigation it found that the Nusselt number of coil side increases with an increase in inlet temperature and VFR of HW.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they found that the parallel flow is less effective than counter flow arrangement. Taraprasad et al 7 have investigated the performance of a TFHE used in domestic heating application. In this investigation it found that the Nusselt number of coil side increases with an increase in inlet temperature and VFR of HW.…”
Section: Introductionmentioning
confidence: 99%
“…19 Experimental research was done on the heat transfer properties of a TFHE used for home heating applications with respect to various design parameters. 20 For a cooling air system, a TTHC air-fuel heat exchanger was suggested to meet the need for thermal protection in advanced aero engines. The temperature of the compressed air was reduced from 823 K to 519 K with a flow rate of 0.0056 kg/s, demonstrating that the heat exchanger successfully cooled the hot air.…”
Section: Introductionmentioning
confidence: 99%